Development and Validation of an Improved Pathological Nodal Staging System in Men with Prostate Cancer. Issue 3 (25th March 2022) - Daskivich, Timothy J.; Luu, Michael; Freedland, Stephen J.; Sandler, Howard; Spratt, Daniel E.; Zumsteg, Zachary S.
Abstract : Purpose: Prostate cancer pathological nodal staging uses a single category for all node-positive patients. We sought to improve risk stratification by creating and validating a novel pathological nodal staging system incorporating number of metastatic lymph nodes (+LNs). Materials and Methods: A total of 118, 450 men who underwent radical prostatectomy for nonmetastatic prostate cancer in the National Cancer Database comprised our development cohort. Multivariable Cox proportional hazards analysis with restricted cubic splines was used to assess the nonlinear association between number of +LNs and overall mortality (OM). A novel staging system based on number of +LNs was derived by recursive partitioning analysis. The staging system was validated for prediction of OM and prostate-specific mortality in 105, 568 men with nonmetastatic prostate cancer undergoing radical prostatectomy from the Surveillance, Epidemiology, and End Results database. Discrimination was assessed via Harrell's c-index. Results: In multivariable Cox analysis, OM risk increased with higher number of +LNs up to 4 (HR 1.30 per each LN+, 95% CI 1.23–1.38), with a nonstatistically significant increase in risk (HR 1.05, 95% CI 0.99–1.11) beyond 4 +LN. In the development cohort, recursive partitioning analysis identified optimal cutoffs at 0 (N0: referent), 1 (N1: HR 1.40, 95% CI 1.25–1.58), 2 (N2: HR 1.67, 95% CI 1.40–1.99), 3–5 (N3a: HR 2.18, 95% CI 0.84–2.60) and ≥6 (N3b: HR 3.00, 95% CI 2.37–3.79) +LNs. In the validation cohort, these groups had markedly different 10-year OM (0+ LNs, N0: 15%; 1+ LN, N1: 35%; 2+ LNs, N2: 43%; 3–5 +LNs, N3a: 52%; and ≥6 +LNs, N3b: 59%; p <0.05) and prostate-specific mortality. The novel staging system improved survival classification over current staging for node-positive patients (optimism-corrected c-index 0.669 [95% CI 0.668–0.671] vs 0.649 [95% CI 0.648–0.651]). Conclusions: Pathological nodal staging in prostate cancer is improved with stratification by number of +LNs.